Business, technological, and social dimensions of computer games : multidisciplinary developments - Cruz-Cunha, Maria Manuela, 1964-; Carvalho, Vitor Hugo, 1979-; Tavares, Paula Cristina Almeida, 1973- (Hershey, PA : Information Science Reference, 2011)
'This book is a collection of the most recent developments in all areas of game development, encompassing planning, design, marketing, business management, and consumer behavior'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Video games industry; Video games -- Design; Video games -- Social aspects